Collagen‐like antimicrobial peptides. Issue 4 (4th November 2016) - Masuda, Ryo; Kudo, Masakazu; Dazai, Yui; Mima, Takehiko; Koide, Takaki
ABSTRACT: Combinatorial library composed of rigid rod‐like peptides with a triple‐helical scaffold was constructed. The component peptides were designed to have various combinations of basic and neutral (or hydrophobic) amino acid residues based on collagen‐like (Gly‐Pro‐Yaa)‐repeating sequences, inspired from the basic and amphiphilic nature of naturally occurring antimicrobial peptides. Screening of the peptide pools resulted in identification of antimicrobial peptides. A structure‐activity relationship study revealed that the position of Arg‐cluster at N‐terminus and cystine knots at C‐terminus in the triple helix significantly contributed to the antimicrobial activity. The most potent peptideRO‐A showed activity against Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis . In addition, Escherichia coli exposed toRO‐A resulted in abnormal elongation of the cells.RO‐A was also shown to have remarkable stability in human serum and low cytotoxicity to mammalian cells. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 453–459, 2016.